Феномен детства в современной русской прозе - Осьмухина, Ольга Юрьевна; Osmukhina, Olga (Східноєвропейський національний університет імені Лесі Українки, 2016)
В статье осмыслена специфика трансформации классической традиции изображения ребенка в прозе Т. Толстой, В. Сорокина, П. Санаева, В. Пелевина, Л. Улицкой, Бориса Акунина. «Детская» тематика в совре-менной прозе реализуется в различных аспектах: символическое изображение детства и младенчества как «утраченного рая» (Т. Толстая, Л. Улицкая); соотнесенность детства с темой одиночества (П. Санаев, А. Гера-симов, Д. Липскеров, Г. Щербакова), свободы и несвободы (В. Пелевин); детская жертвенность и слияние с вечностью (В. Сорокин); утрата детскости посредством примеривания маски (Борис Акунин). Установлено, что детская тема расширяется и углубляется, переносится из сферы сугубо психологической в область метафизическую, связывается с проблемой восприятия ребенком основополагающих нравственных ценностей.In the article is investigating the specificity of transformation classic tradition of child demonstration's in the fiction of T. Tolstaya, V. Sorokin, P. Sanaev, V. Pelevin, L. Ulitskaja, Boris Akunin. The «children’s» subjects in modern prose is realized in various aspects: the symbolical image of the childhood and infancy as «lost paradise» (T.Tolstaja, L. Ulitskaja); correlation of the childhood to subject matter loneliness (P. Sanaev, A. Gelasimov, D. Lipskerov), freedom and loss of freedom (V. Pelevin); children's sacrifice and merge to eternity (V. Sorokin); loss of childishness through uses of a masks (Boris Akunin).Found that the children’s theme extends and deepens, shifts from a purely psychological in the metaphysical, is associated with the problem of perception of the child the fundamental moral values.
The phenomenon of Childhood in Modern Russian Prose
Keywords: детство; образ; рефлексия; роман; традиция; childhood; literary image; reflection; romance; tradition